Nanoengineered Erythrovesicles: Camouflaged Capecitabine as a Biomimetic Delivery Platform - Payghan, Dr. Santosh Ambadas (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: Circulation half-life has become one of the major design considerations in nanoparticulate drug delivery systems. By taking cues for designing long circulating carriers from natural entities such as red blood cells (RBCs) has been explored for many years. Among all the cellular carriers including leukocytes, fibroblast, islets, and hepatocytes, RBCs offer several distinctive features. Nanovesicles (NVs) represent a novel transporter for cell signals to modify functions of the target cell. Therefore, NVs play many roles in both physiological and pathological process. Materials and Methods: This report highlights biogenesis, composition, and biological rules of erythrocytes derived NVs (EDNVs). Furthermore, we address utilization of EDNVs as novel drug delivery cargo as well as therapeutic target. Result and Discussion: EDNVs are biocompatible, biodegradable, efficient drug loading target specificity, and prolonged biological half-life. It is also rich in phospholipids, proteins, lipid raft, and hemoglobin. In this study, nanosize lipoprotein membrane vesicles (EDNVs) bearing capecitabine were prepared by sonication method. Conclusion: Developed capecitabine nano erythrosomes conjugate formulation were preliminary optimized on the basis of vesicle morphology, size and size distribution, loaded drug concentration, and in vitro release studies.